2022
DOI: 10.3390/jof9010024
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Fundamental miRNA and Gene Expression during the Barley-Piriformospora indica Interaction

Abstract: The interactions between plants and microorganisms, which are widely present in the microbial-dominated rhizosphere, have been studied. This association is highly beneficial to the organisms involved, as plants benefit soil microorganisms by providing them with metabolites, while microorganisms promote plant growth and development by promoting nutrient uptake and/or protecting the plant from biotic and abiotic stresses. Piriformospora indica, an endophytic fungus of Sebacinales, colonizes the roots of a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, oxygen level is involved in many important signaling responses and is beneficial to plants by supporting cellular proliferation, physiological function, and viability [48,49]. Similarly, transcriptome analysis of Piriformospora indica indicated that the DEGs with the greatest changes were concentrated in oxidoreductase activity and ion transmembrane transporter activity [50]. KEGG enrichment analysis was also used to understand the DEGs after JRF11 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxygen level is involved in many important signaling responses and is beneficial to plants by supporting cellular proliferation, physiological function, and viability [48,49]. Similarly, transcriptome analysis of Piriformospora indica indicated that the DEGs with the greatest changes were concentrated in oxidoreductase activity and ion transmembrane transporter activity [50]. KEGG enrichment analysis was also used to understand the DEGs after JRF11 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, hvu-miR6214 was predicted to target genes involved in photosynthesis pathway, cell division and hormone activity. Therefore, it is associated with plant development and growth 47 . The results showed that hvu-miR159a and hvu-miR159b were associated with some of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA profiles involved in the interaction between barley and P. indica have been extensively studied, identifying 42 miRNAs through transcriptome sequencing and annotation analysis. These miRNAs are predominantly associated with the target genes that are implicated in cell division, auxin signal reception, and hormone response, thus exerting a pivotal role in the organism's adaptive response to both biotic and abiotic stressors [105]. Furthermore, the effector molecule PIIN_08944 originating from P. indica has been confirmed to interfere with the salicylic acid (SA)-mediated basal immune responses of the host plant [106].…”
Section: Modulation Of Hormone Metabolism Pathwaysmentioning
confidence: 99%